A novel interface layer for inverted perovskite solar cells fabricated in ambient air under high humidity conditions - Choi, Fatma Pinar Gokdemir; Alishah, Hamed Moeini; Bozar, Sinem; Doyranli, Ceylan; Koyuncu, Sermet; San, Nevim; Kahveci, Cihangir; Rodop, Macide Canturk; Arvas, Melih Besir; Gencten, Metin; Sahin, Yucel; Gunes, Serap (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
A novel benzotriazol based small molecule (2-hexyl-4,7-bis(5'-hexyl-2,2'-bithien-5-yl)-2H-1,2,3-benzotriazole) BTBT was synthesized by Suzuki coupling reaction and was successfully employed in planar inverted perovskite solar cells with ITO/BTBT/PEDOT:PSS/CH3NH3PbI3-xCl(x)/PCBM/Al configuration. Fabrication processes, including the spin coating of the perovskite layer, were performed in ambient air, under high humidity conditions (>60%). BTBT/PEDOT:PSS bilayer notably improved the power conversion efficiencies (PCE) from 9.65% to 11.6%, which corresponds to an increase of 20%.
Keywords: Benzotriazol based small molecule; Hole transport layer; Electron blocking layer; Planar perovskite solar cells; Inverted structure; Perovskite grain size; PROBE FORCE MICROSCOPY; PLANAR; EFFICIENT; PERFORMANCE; CHALLENGES; FILM; Energy & Fuels